Edukasi Konsumsi Air Rebusan Daun Sirsak terhadap Pengetahuan Pasien Hipertensi - Nia Anggraini Adam; Rahmat H. Djalil; Faradilla Miftah Suranata (PPNI UNIMMAN, 2025)
Hypertension is a disorder of the blood vessels, which causes the supply of oxygen and nutrients to the body to be blocked. Providing education on consuming boiled soursop leaves can help and increase the knowledge of hypertensive patients in controlling or lowering blood pressure. This purpose is to determine the Effect of Education on Consuming Boiled Soursop Leaves on the Knowledge of Hypertensive Patients. This type of research is quantitative research using a one-group pretest-posttest design. The sample consisted of 30 patients obtained using the Arikunto formula. Sampling using purposive sampling. The results of the study based on the McNemar test, the p value was 0.000, which was smaller than the significant value (a = 0.05), thus H0 was rejected and Ha was accepted, which means that there is an Effect of Providing Education on Consuming Boiled Soursop Leaves. The conclusion is that there is an effect of providing education on consuming boiled soursop leaves on the knowledge of hypertensive patients in. The results of this study are expected to be able to utilize the results that have been obtained.